Occupational therapy practice education: A perspective from international students in the UK. (2nd January 2022) - Law, Ching Pan; Masterson-Ng, Shirley; Pollard, Nick
Abstract: Background: Numbers of international students enrolling on occupational therapy (OT) courses in Western institutions have increased. Previous examination of these students' experience of practice education is limited. Objective: To explore the opportunities and challenges experienced by international students in OT practice education. Methods: This study adopted a phenomenological approach, recruiting six individuals from three UK universities. Data from semi-structured interviews was given thematic analysis for result interpretation. Results: Participants identified learning OT in the workplace, working in a multidisciplinary team and personal and professional development as practice education opportunities. Language difficulties, differences in communication styles, multiple cultural differences and unfamiliarity with the National Health Service (NHS) were the main challenges. Good practice educators and supportive team members were the main contributors to positive placement experiences. Conclusions: Participants gained knowledge and skills from practice education that existing healthcare literature suggests they are expected to attain. Several challenges were highlighted regarding participation in practice education. The findings reveal a need to enhance practice educators' skills in supervising international students. Universities are recommended to invest time and resources in supporting the learning needs of these students. Significance: The first study to present international students views on OT pre-registration practice placements in the UK.